PSYCHOLOGICAL EFFECTS OF CYBER HARASSMENT AMONG HIGHER EDUCATION STUDENTS (Contemporary Journal of Social Science Review, 2025)
Cyber harassment is a significant psychological issue among higher education students because of the popularity of digital communication media. This study analyzed the psychological impacts of cyber harassment on students at universities and colleges examining emotional distress, anxiety, depression, self-esteem, and academic functioning. It used a cross-sectional study with a sample  comprising 150 students aged 18 to 26 years who were enrolled in three higher education institutions consisting of two universities and one degree college. A Cyber Harassment Impact Questionnaire (CHIQ), Depression Anxiety Stress Scale (DASS-21), and a Demographic Information Form were used to collect the data. The findings indicate that students who were victims of cyber harassment recorded very high rates of anxiety, depressive symptoms, emotional lability, and lower self-esteem. The psychological effect were identified as more intense in female students, Whereas,  male students more often showed anger and behavioral problems. The paper highlights that greater attention should be paid to the implementation of institutional awareness campaigns, online safety courses, and mental health services to help reduce the negative effects of cyber bullying on the psychological well-being and academic performance of students.